Acute necrotising pancreatitis and acalculous cholecystitis: a rare presentation of leptospirosis - Mohd Sazlly Lim, Sazlyna; Hoo, Fan Kee; Wan Sulaiman, Wan Aliaa; Ramachandran, Vasudevan; Ching, Siew Mooi (Pakistan Medical Association, 2014)
Leptospirosis typically presents with fever and thrombocytopenia, with or without jaundice. Acute necrotising pancreatitis and acalculous cholecystitis are rare presentations of this spirochetal infection. Here is the case of necrotising pancreatitis and acalculous cholecystitis associated with leptospirosis in an elderly patient. Leptospirosis was diagnosed by serological tests and abdominal CT imaging. The patient was successfully treated medically with intravenous antibiotics (imipenem and ceftriaxone) and proper hydration.